Electrochemistry of silicon in chloro-fluoride and carbonate melts - Devyatkin S.V. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The electrochemical behavior of K2SiF6 in chloro-fluoride melts and that of SiO2 in carbonate melts has been studied. Silicon, titanium silicides, boron silicide and ternary compounds Ti-Si-B have been deposited from chloro-fluoride melts. Only SiC was deposited from carbonate-silica melts under carbon dioxide atmosphere (that is, excessive pressure of CO2).